Evidence of Helicobacter sp. in dental plaque of captive dolphins (Tursiops gephyreus) - Goldman, Cinthia Gabriela; Loureiro, Julio D.; Quse, Viviana; Corach, Daniel; Calderon, Enrique; Caro, Ricardo A.; Boccio, José; Heredia, Sergio Rodríguez; Di Carlo, Maria Beatriz; Zubillaga, Marcela Beatriz (Journal of Wildlife Diseases)
Gastrointestinal lesions have been extensively reported in wild and captive marine mammals. However, their etiology remains unclear. In humans and other animals, chronic gastritis and peptic ulcers have been associated with Helicobacter sp. Therefore, the aim of our study was to investigate the presence of Helicobacter sp. in the gastric juice, dental plaque, and saliva of marine mammals living in a controlled environment. Five dolphins (Tursiops gephyreus), one killer whale (Orcinus orca), one false killer whale (Pseudorca crassidens), three sea lions (Otaria flavescens), two elephant seals (Mirounga leonina), and two fur seals (Arctocephalus australis) were studied. Saliva, dental plaque, and gastric juice samples were examined for Helicobacter sp. using polymerase chain reaction. None of the gastric juice or saliva samples were positive for Helicobacter sp. However, Helicobacter sp. DNA was detected in dental plaque from two dolphins, suggesting the oral cavity might be a reservoir of this bacterium. Fil: Goldman, Cinthia Gabriela. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Houssay; Argentina. Universidad de Buenos Aires. Facultad de Farmacia y Bioquímica; Argentina Fil: Loureiro, Julio D. Fundación Mundo Marino; Argentina Fil: Quse, Viviana. Fundación Mundo Marino; Argentina Fil: Corach, Daniel. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Houssay; Argentina. Universidad de Buenos Aires. Facultad de Farmacia y Bioquímica; Argentina Fil: Calderon, Enrique. Fundación Mundo Marino; Argentina Fil: Caro, Ricardo A. Universidad de Buenos Aires. Facultad de Farmacia y Bioquímica; Argentina Fil: Boccio, José. Universidad de Buenos Aires. Facultad de Farmacia y Bioquímica; Argentina Fil: Heredia, Sergio Rodríguez. Fundación Mundo Marino; Argentina Fil: Di Carlo, Maria Beatriz. Universidad de Buenos Aires. Facultad de Farmacia y Bioquímica; Argentina Fil: Zubillaga, Marcela Beatriz. Consejo ...